2004
DOI: 10.1097/01.asn.0000109672.83594.02
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Signal Transducer and Activator of Transcription Signaling Pathway in Renal Proximal Tubular Cells by Albumin

Abstract: Abstract. Renal proximal tubular cells activated by reabsorption of protein are thought to play significant roles in the progression of kidney diseases. It was hypothesized that the signal transducer and activator of transcription (STAT) proteins may be activated by proteinuria in proximal tubular cells. To test this hypothesis, murine proximal tubular cells were treated with albumin (30 mg/ml medium) for various lengths of time. The results showed that albumin could activate Stat1 and Stat5 within 15 min in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 56 publications
(44 reference statements)
3
56
0
Order By: Relevance
“…This phenomenon appears to be relatively general since ROS mediate induction of Jak-2 activation in tissues such as cardiac myocytes and vascular smooth muscle cells (34 -36) as well as kidney cells (12,14,15,32). We did not test whether ROS could further augment the signaling to Stat-3 in our Jak-2-overexpressing cells but we did show that Jak-2 overexpression induced ROS production in mesangial cells, especially those cultured in high glucose medium.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This phenomenon appears to be relatively general since ROS mediate induction of Jak-2 activation in tissues such as cardiac myocytes and vascular smooth muscle cells (34 -36) as well as kidney cells (12,14,15,32). We did not test whether ROS could further augment the signaling to Stat-3 in our Jak-2-overexpressing cells but we did show that Jak-2 overexpression induced ROS production in mesangial cells, especially those cultured in high glucose medium.…”
Section: Discussionmentioning
confidence: 70%
“…We focused on these results because the activation of Jak/Stat signaling pathways can be implicated in both tubulointerstitial fibrosis and epithelial to mesenchymal transition in several conditions, including diabetes, in animal models (11)(12)(13). Similarly, Jak/Stat activation is reported in rat glomerular cells exposed to high glucose (14,15) and may be important in the glomerular transforming growth factor-␤ activation and fibronectin accumulation critical for extracellular matrix deposition in early diabetic nephropathy (15).…”
mentioning
confidence: 99%
“…A link also has been made between induction of NF-B activity by protein load and mitogen-activated protein kinases, including p38 (25) and extracellular signal-regulated kinase 1 and 2 (ERK1/ERK2) (29) that are involved in chemokine synthesis. In support of the notion of protein overload as a key activator of signaling in proximal tubule is the finding that albumin activated the signal transducer and activator of transcription (STAT) proteins in cultured proximal tubular cells (30). Because the STAT pathway is the principal mechanism that converts the signal from a wide array of cytokines and growth factors into gene expression programs that regulate cell proliferation, differentiation, survival, and apoptosis (31), it was suggested that albumin may stimulate proximal tubular cells in the manner of a cytokine (32).…”
Section: Glomerular Proteinuria As Signal For Interstitial Inflammatimentioning
confidence: 97%
“…In vitro treatment of PTC with albumin leads to activation of the JAK/STAT pathway and inflammation, cell differentiation, fibrosis, and apoptosis (230). Furthermore, albumintreated PTCs demonstrate reduced levels of antioxidants catalase and GPx, and levels were brought back to normal with antioxidant (NAC) treatment.…”
Section: B Ros and The Glomerular Basement Membrane (Gbm)mentioning
confidence: 98%